Sedimentology and fluvial styles of the uppermost Cretaceous continental deposits of the Austral-Magallanes Basin, Patagonia, Argentina (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The sedimentary infill of the Austral-Magallanes Basin since the onset of its foreland stage in the Lago Argentino region is dominated by deep-marine and coastal deposits. However, during the Late Cretaceous the basin accumulated a thick and poorly known continental sedimentary succession, which has received different lithostratigraphic names. The aim of this work is to characterize the here defined Uppermost Cretaceous Continental Deposits (UCCD) from a detailed facies and architectural analysis, as well as the resulting stacking pattern. Seven Facies Associations (FAs) were discriminated in order to define the sedimentary paleoenvironments: FA1, gravelly sheet bodies; FA2, tabular bodies of conglomerates with mud rip-up clasts; FA3, complex tabular sandy bodies; FA4, simple tabular sandy bodies; FA5, tabular bodies of structureless sandstones; FA6, heterolithic deposits; and FA7, fine-grained deposits. Three different fluvial styles were recognized: meandering systems dominated by avulsion and meander abandonment processes (fluvial style a), braided systems (fluvial style b), and meandering systems dominated by overbank flood processes (fluvial style c). The stacking pattern of the FAs allowed to divide the UCCD into two major depositional stages related to the accommodation space vs sediment supply (A/S) ratio. Stage I is characterized by the alternation of fluvial styles a and b, while the Stage II is represented by the alternation of fluvial styles c and b, and the Stage III is characterized entirely by fluvial style c deposits. Although the UCCD are considered as a whole within a framework of low A/S ratio, several high frequency variations were recognized. The Stage I records seven high frequency intervals of which four are characterized by high A/S ratio interrupted by three events of low A/S. While the stage II is represented by six high frequency periods of low A/S ratio and other five high frequency events of high A/S ratio. The Stage II is considered as deposited in a relative higher A/S context in comparison with the Stage I, based on the behavior of the moderate to high sinuosity meander fluvial systems. Finally, the Stage III is represented entirely by a high frequency low A/S ratio event.